A Case Study of Scrap Tire Disposal in North Carolina - Williams, Vereda Johnson (Journal of Environmental Science and Engineering Technology, 2013)
North Carolina law states that whole tires were banned from landfills as of March 1, 1990. Used tires disposed in landfills do not decompose for several years and tend to disrupt landfill covers by rising to the surface. In 2011-12 approximately 145 thousand tons of scrap tires were reported in North Carolina. These tires were used for fuel, either in shredded form known as tire-derived fuel (TDF) or whole, depending on the type of combustion device. Best practices have shown that tires need to be reduced in size to fit in most combustion units. TDF is one of several alternatives to prevent newly generated scrap tires from inappropriate disposal in tire piles, and for reducing or eliminating existing tire stockpiles. Scrap tires represent both a disposal problem as well as a resource opportunity. There are several potentially negative environmental and health impacts associated with scrap tire piles. This study focuses on an examination of North Carolina’s disposal and usage of scrap tires.